A The Influence Of Altruistic Leadership And Achievement Motivation On The Performance Of Madrasah Supervisors In North Aceh District - Ilyas, Muslem; Manumanoso Prasetyo, Muhammad Anggung (The Faculty of Education and Teaching Training, 2024)
Teachers' abilities influence the effectiveness of learning, but their performance could be better, reducing the quality of schools. The 2015-2021 Teacher Professional Test showed that 81% of teachers still needed to achieve the minimum score. The poor performance of supervisors due to their small number also exacerbates the problem. Improving the quality of supervision through altruistic leadership, motivation, professionalism, and work culture is crucial to improving the quality of education in Indonesia. This study investigates whether there is a relationship between altruistic leadership and achievement motivation on the performance of supervisors of North Aceh District Ibtidayah Madrasahs. This study used a mixed method sequential explanatory approach with a Path Analysis research model with an associative research type. Data were collected through questionnaires from 150 respondents in 14 A accredited Madrasah Ibtidayah. This study found that 1) altruistic leadership on supervisor performance (original sample) is 0.630, which means there is a positive influence between the two variables. Then, the resulting t-count value is 7.185, which means that these results are said to be significant because the t-count value is greater than the t-table (7.185> 1.96), or it can be said that the hypothesis is accepted. 2) the effect of achievement motivation variables on supervisor performance (original sample) is 2.224, which means there is a positive influence between the two variables. Then, the resulting t-count value is 2.511, which means that these results are said to be significant because the t-count value is greater than the t-table (2.511> 1.96), or it can be said that the hypothesis is accepted. This study concludes that a significant relationship exists between altruistic leadership and improving supervisors' performance, and achievement motivation has a positive influence. A significant relationship exists between improving supervisors' performance in North Aceh Regency. Kemampuan guru mempengaruhi efektivitas pembelajaran, tetapi kinerja mereka bisa lebih baik, sehingga mengurangi kualitas sekolah. Uji Profesi Guru tahun 2015-2021 menunjukkan bahwa 81% guru masih perlu mencapai nilai minimum. Kinerja pengawas yang buruk karena jumlah mereka yang sedikit juga memperparah masalah ini. Meningkatkan kualitas pengawasan melalui kepemimpinan altruistik, motivasi, profesionalisme, dan budaya kerja sangat penting untuk meningkatkan kualitas pendidikan di Indonesia. Penelitian ini menyelidiki apakah ada hubungan antara kepemimpinan altruistik dan motivasi berprestasi terhadap kinerja pengawas Madrasah Ibtidayah Kabupaten Aceh Utara. Penelitian ini menggunakan pendekatan eksplanatori sekuensial metode campuran dengan model penelitian Analisis Jalur (Path Analysis) dengan jenis penelitian asosiatif. Data dikumpulkan melalui kuesioner dari 150 responden di 14 Madrasah Ibtidayah yang terakreditasi A. Penelitian ini menggunakan pendekatan eksplanatori sekuensial metode campuran dengan model penelitian Path Analysis dengan jenis penelitian asosiatif. Data dikumpulkan melalui kuesioner dari 150 responden di 14 Madrasah Ibtidayah terakreditasi A. Penelitian ini menemukan bahwa 1) kepemimpinan altruistik terhadap kinerja pengawas (original sample) sebesar 0,630 yang berarti terdapat pengaruh positif antara kedua variabel tersebut. Kemudian, nilai t-hitung yang dihasilkan sebesar 7,185, yang berarti hasil tersebut dikatakan signifikan karena nilai t-hitung lebih besar dari t-tabel (7,185 > 1,96), atau dapat dikatakan hipotesis diterima. 2) pengaruh variabel motivasi berprestasi terhadap kinerja supervisor (original sample) sebesar 2,224 yang berarti terdapat pengaruh positif antara kedua variabel tersebut. Kemudian, nilai t-hitung yang dihasilkan sebesar 2,511 yang berarti hasil tersebut dikatakan signifikan karena nilai t-hitung lebih besar dari t-tabel (2,511 > 1,96), atau dapat dikatakan hipotesis diterima. Penelitian ini menyimpulkan bahwa terdapat hubungan yang signifikan antara kepemimpinan altruistik dengan peningkatan kinerja supervisor, dan motivasi berprestasi memiliki pengaruh yang positif. Terdapat hubungan yang signifikan antara peningkatan kinerja pengawas di Kabupaten Aceh Utara.